Strategi Dan Rencana Implementasi CRM Dalam Menghadapi Preferensi Pelanggan Perusahaan Farmasi Di Indonesia - Catharina Cita Padmasari; Nila Armelia Windasari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Customer Relationship Management in pharmaceutical industry is used to manage and maintain relationship with customers, most importantly healthcare professionals (HCP). Reassessing and improving customer engagement in light of the environment's shifting dynamics will inevitably lead to better access for patients as the final consumers of pharmaceuticals. Initially, covid-19 pandemic social restrictions created new engagement model that depended solely on digital engagement. However, covid-19 instances are declining, and pandemic recovery is accelerating. There are shifting engagement dynamic to be hybrid engagement in Indonesia HCP as well. This opportunity enables pharmaceutical companies to understand HCP’s current preferences. This research aims to build CRM Engagement Strategy with understanding the customer’s perspectives and moderated with internal stakeholders' capabilities and external forces during post-pandemic recovery using case-study approach. The primary research found that pharmaceutical companies have enabled hybrid model that aligns with flexible preferences of HCP that combine face-to-face and digital interactions that address data privacy concerns of HCPs. The result of this research is importance of building CRM arrangement strategy in light of post-pandemic HCP’s preferences. Keywords : customer relationship management; pharmaceutical companies; post-pandemic recovery